Exponent matrices and topological equivalence of maps - Fedorenko, V.; Kirichenko, V.; Plakhotnyk, M. (Algebra and Discrete Mathematics, 2007)
Conjugate classes of continuous maps of the interval [0,1] into itself, whose iterations form a finite group are described. For each of possible groups of iterations one to one correspondence between conjugate classes of maps and equivalent classes of (0,1)-exponent matrices of special form is constructed. Easy way of finding the quiver of the map in terms of the set of its extrema is found.